(untitled) (Research, Society and Development, 2026)
Rural education presents historical, social, and pedagogical specificities that require contextualized teaching practices aligned with the realities of rural communities. Among the main challenges faced by rural schools is the organization of pedagogical work in multigrade classrooms, where students of different ages, grade levels, and learning stages share the same educational space. This article aims to analyze the challenges and possibilities of effective literacy practices in multigrade classrooms in rural schools, with emphasis on teacher education, the exchange of teaching experiences, and collaborative practices as strategies to strengthen the teaching-learning process. The study adopts a qualitative approach, characterized as a bibliographic and reflective research, grounded in authors who discuss rural education, multigrade teaching, literacy, and teacher professional development. Special emphasis is given to the contributions of Andrade (2025), who highlights collaborative teacher education through the Lesson Study method as a powerful strategy for improving pedagogical practices in complex educational contexts. The findings indicate that, despite structural and pedagogical limitations, multigrade classrooms can become meaningful learning spaces when supported by intentional teaching practices, continuous teacher education, and the valuing of collaborative professional experiences. The study reinforces the importance of recognizing multigrade education not as a limitation, but as a pedagogical possibility for promoting equitable and contextualized literacy in rural schools.